KAPASITAS KELOMPOK TANI DI DESA UUWAN KECAMATAN DUMOGA BARAT KABUPATEN BOLAANG MONGONDOW - MANITIK, ENGLIN FERLINA; KIYAI, BURHANUDDIN; RURU, JOORIE (JURNAL ADMINISTRASI PUBLIK, 2021)
The capacity of farmer groups is one of the things that can help the welfare of the existing village of Uuwan. The existence of ani group in Bolaang Mongondow Regency basically greatly affects the improvement of the economy and the welfare of the community, this is seen from the number of workers and the size of land in the sector. Empowerment of farmers is all efforts to improve the ability of farmers to carry out better farming activities through education and training, counseling and assistance in developing systems and means of marketing for cultivated agricultural products and guaranteeing the extent of agricultural land, easy access to science, technology and information and strengthening farmer institutions. The results of the 5 existing informants can be concluded that the welfare of the Uuwan village community is good and not a little from agricultural products. And also from the social aspect, In Uuwan village, social life in the community is already high. And in education also in Uuwan Village, many have been educated up to a Bachelor's degree compared to a few years ago for only a few high school graduates, but now many parents who are farmers are able to send their children to the strata 1 level even many are already working . Keywords: Capacity, Farmer Groups, Empowerment